Perancangan Antena Transparan Berbasis Teknologi LTE untuk Komunikasi Antar Mobil - Saputra, M. Feri; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Along with the development of fast wireless technology, car to car communication (C2C) has been widely used in communication between vehicles for internet access and safe driving control. During the last few years, the design of antennas using transparent materials has attracted the interest of researchers. This is due to the low thickness and light structure of transparent materials compared to conventional designs. In this study, the transparent antenna based on LTE technology for C2C communication is developed. This antenna works at 1.8 GHz with return loss of -27.98 dB. The antenna simulation was performed using CST Microwave Studio. Keywords – Transparent antenna, LTE technology, C2C